Die juridiese faset van dissipline - Robbertse, Johannes Hendrik (2014)
M.Ed. === The purpose of this study was to determine the educator's perception on the importance of the juridical facet of discipline. It also aimed to inform readers what the rights and duties of parents, teachers and children as far as discipline is concerned. The study is presented as follows: * Chapter 1 : Introduction * Chapter 2 '* Chapter 3 * Chapter 4 * Chapter 5 FINDINGS A study of literature on the juridical facet of discipline. The research plan. The assimilation and interpretation of the empirical data. Summary, conclusion and recommendations. * More woman than men had facet plays an important discipline. the opinion that the juridical part in the application of * Afrikaans mother tongue speakers valued the juridical facet higher than English mother tongue speakers. * More teachers than parents were of the opinion that the juridical facet plays an important role in the application of discipline. * Involvement of educationists either at primary- or secondary schools didn't influence their perception on the importance of the juridical facet. * The age of an educationist did have an influence on his view of the juridical facet of discipline. * Flat tenants regarded the juridical facet of discipline far more important than home residents did. * Christian educationists regarded the facet more important than non-Christians. * The mari tal status of educationists didn't have an influence discipline. on their perception of the juridical facet of * As far as income was concerned it became clear that the lower the income group the more important the juridical facet of discipline was regarded. CONCLUSION Ignorance of the law proves in many cases to be a problem in the application of discipline. Teachers and parents must therefore be thorougly informed about their roles in the juridical facet of discipline and must realize that they are partners in the disciplining of the child (Bondesio, 1989: 107) • It thus became evident that the juridical facet of discipline is regarded as highly important by most educationist